Dynamic profiles of 25 serum biomarkers in acute myocardial infarction - Ai, Xuefeng; Wang, Yuanyuan; Jiang, Mingwei; Han, Qianyu; Geng, Hongli; Wang, Cheng; Chen, Jirui; Xue, Lei; Jin, Yuxiang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute myocardial infarction (AMI) is a leading cause of cardiovascular mortality and perioperative complications in the elderly (>65 years). However, existing clinical biomarkers (e.g., troponin) still lack sufficient sensitivity for ultra-early diagnosis. A comprehensive understanding of the dynamic changes in serum biomarkers post-AMI is crucial for developing novel diagnostic strategies.MethodsA rat AMI model was established by surgical ligation of the left anterior descending (LAD) coronary artery. Cardiac function was evaluated via echocardiography and triphenyltetrazolium chloride (TTC) staining at 24 h post-AMI. Blood samples were collected at baseline (pre-anesthesia) and at 1, 2, 6, 12, 24, and 48 h post-LAD ligation. Serum levels of 25 biomarkers were measured by ELISA, including: α-smooth muscle actin (α-SMA), aminopeptidase N (ANPEP), B-type natriuretic peptide (BNP), C-C chemokine receptor type 2 (CCR2), C-reactive protein (CRP), connective tissue growth factor (CTGF), C-X-C motif chemokine ligand 16 (CXCL16), cystatin C (Cys), dopamine D2 receptor (D2D), glucagon-like peptide-1 (GLP-1), homocysteine (Hcy), chemokine-like factor 1 (CKLF1), high-sensitivity troponin I (hs-TnI), interleukin-1β (IL-1β), interleukin-6 (IL-6), lipoprotein(a) (Lp-α), monocyte chemoattractant protein-1 (MCP-1), matrix metalloproteinase-9 (MMP-9), NOD-like receptor family pyrin domain-containing 3 (NLRP3), plasminogen activator inhibitor-1 (PAI-1), S100 calcium-binding protein A8 (S100A8), solute carrier family 31 member 1 (copper transporter, SLC31A1), tissue inhibitor of metalloproteinases-1 (TIMP-1), tumor necrosis factor-α (TNF-α), and vascular endothelial growth factor A (VEGF-A).ResultsAt 24 h post-AMI, LVEF was significantly decreased in the AMI group (63.84 ± 2.48% vs. 38.83 ± 2.62%, p < 0.001), with an infarct size of 28.70 ± 1.43%. A total of 25 blood biomarkers potentially associated with AMI were detected. Among them, 17 biomarkers showed rapid elevation within 1 h post-AMI (excluding IL-6, TNF-α, ANPEP, D2D, CXCL16, Lp-α and α-SMA). IL-6, TNF-α and ANPEP exhibited significant elevation at 2 h post-AMI, while CXCL16 showed obvious elevation at 6 h and α-SMA demonstrated significant elevation at 12 h. However, S100A8, GLP-1, MMP-9 and NLRP3 showed a decrease at 2 h, although their overall trend within 48 h was upward. Lp-α and D2D remained below baseline levels throughout the observation period, with both showing levels below baseline at 1 h post-AMI. They returned to baseline levels at 12 h and 2 h respectively, followed by rapid decreases againConclusionThis study is the first to systematically characterize the dynamic profiles of 25 serum biomarkers following AMI in rats, revealing that: (1) IL-1β, S100A8, BNP, SLC31A1 and Cys may serve as an ultra-early (1 h) diagnostic panel (increase of over 70% at 1 h); (2) the delayed elevation of α-SMA and CXCL16 may be associated with the initiation of myocardial repair; (3) the suppression of Lp-α and D2D might reflect compensatory protective mechanisms.